Simulation and energy optimization of a pulp and paper mill – Evaporation plant and digester - Ji, Xiaoyan; Lundgren, Joakim; Wang, Chuan; Dahl, Jan; Grip, Carl-Erik (Applied Energy, 2012)
A detailed mathematical process integration model of a pulp and paper mill in the Northern Sweden has been developed. The main objective of this work has been set to describe the practical development of the model with particular emphasis on the development of the digester and evaporation plant sub-models. Actual plant measurements have been used to validate the model. By implementing the sub-models into the complete plant model, the influence of different operation parameters on the overall plant performance has been investigated. Furthermore, introductory studies with the main objective to minimize the plant energy cost have been carried out. Validerad;2012;20120213 (xiajix);Konferensartikel i tidskrift; Energy Solutions for a Sustainable World - Proceedings of the Third International Conference on Applied Energy, May 16-18, 2011 - Perugia, Italy